Conducting and characterizing femto flow electrospray ionization. Issue 6 (23rd February 2022) - Li, Huishan; Allen, Nicholas; Li, Mengtian; Li, Anyin
Abstract : A submicron emitter tip and relay ESI configuration enable the measurement of the ESI flow rate in the femto liter per minute (fL min −1 ) range. Abstract : Femto flow electrospray ionization (ESI) with flow rates ranging from 240 fL min −1 to the low pico level (<10 pL min −1 ) was conducted and measured using a submicron emitter tip and relay ESI configuration. Signature analyte ion current intensities and profiles were observed. The obtained flow rate and ionization current enabled size calculation for initial charged nanodroplets.